Analysis and evolution of the time marks registered in the “100 m manikin tow with fins” event - Sanz Arribas, Ismael; Gento, Angel; Pino , Jessica; Dominguez, Ana; Cano-Noguera, Francisco (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study is to know the evolution of the time marks recorded in the "100 m manikin tow with fins" event. In addition, it also aims to identify those factors that may have caused changes in the evolution of the marks obtained in this event. For this purpose, we have compiled the three best times in the absolute category (both male and female) achieved in 13 Lifesaving Spanish Winter Championships. Specifically, the time of period analyzed in this study is from 2008 to 2020. The results show that, throughout the period studied, the marks accredited in the "100 m manikin tow with fins" event have shown a positive evolution. The evolution has been more pronounced in the female category than in the male category. The average of the three best marks of the female category has improved 9,41 seconds (14.56%) while the men’s category has improved 5,97 seconds (11.12%). In addition, the elimination of the rule requiring the manikin’s breathing airway to remain unobstructed during the event and the use of the latest generation of fins have probably influenced in the evolution of the marks obtained in this event.